Предмет: Алгебра,
автор: 2007198120016
Преобразуйте выражение :
А) (1/2х+6)^2
Б) (0,2х-3)(0,2х+3)
СРОЧНО ПОЖАЛУЙСТА
Ответы
Автор ответа:
1
Ответ:
Объяснение:
a) (1/2 x+6)^2=1/4 x^2+2*1/2x*6+36=0.25x^2+6x+36
b) (0,2х-3)(0,2х+3)=(0.2x)^2-3^2=0.04x^2-9
2007198120016:
это правильно ??
Похожие вопросы
Предмет: Русский язык,
автор: kostello1
Предмет: Английский язык,
автор: 3880084
Предмет: Русский язык,
автор: wankoover301
Предмет: Литература,
автор: DashaMartsakova
Предмет: Математика,
автор: Рима25